EXPERIÊNCIAS ACADÊMICAS DO CURSO DE FISIOTERAPIA NOS CENTROS DE ATENÇÃO PSICOSSOCIAL (CAPS) DE IJUÍ/RS - Schneider, Juliana; Pretto, Luciana M.; Riva, Denise; Wendland, Juliana; Weber, Cassiane; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo